ä¸¹æˆŽå¸ƒæ‹‰å›½ç«‹å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯ä¸“ä¸š2015å±Šå¦ç”Ÿ ä½¿ç”¨åè¯â€œåŽæ¥â€å’Œâ€œä»¥åŽâ€çš„åè¯¯åˆ†æž - Mayasari, A?an Rifanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract In Mandarin learning, grammar has a very important role. The noun is one of the most important parts of grammar, including the noun "houlai" and "yihou". "Houlai" and "yihou" also include the word synonym. Synonyms are words that contain the same meaning. In Mandarin learning, "houlai" and "yihou" have the same meaning, but each use of the word has different usage, so that the learners have difficulty in learning it. The author analyzes the mistakes on Student Generation 2015 Prodi Mandarin Education Faculty of Teacher Training and Education University of Tanjungpura. The author only examines two types of errors, namely misuse and misfire to examine their errors. The result of the research shows that the errors of the use of "houlai" and "yihou" in the 2015 Students Program of Mandarin Language Education Program of Tanjungpura University are 31.43% for "houlai" error (misuse 21.84%,    9.59% error rate) For "yihou" error 33.39% (misuse of 9.82%, misconduct of 23.57%). The cause of the error is due to the lack of understanding of how to use "houlai" and "yihou" in a sentence and assume that "houlai" and "yihou" have the same meaning. Keywords: The noun "Houlai" and "Yihou", Error Analysis, Cause of Error